Studi tentang Peran Entrepreneurial Marketing dalam Meningkatkan Business Performance UMKM di Masa Pandemi Covid-19 - Setiyaningrum, Ari; Ramawati, Yussi; Hidayat, Herlin (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2022)
Abstract: The entrepreneurial marketing approach is a strategic choice that can be adopted by SME actors to continue to survive, especially in the midst of the Covid-19 pandemic situation. This study aims to identify which dimensions of entrepreneurial marketing have an important role in improving SME business performance in the creative economy industry during the Covid-19 pandemic. In particular, this study examines whether the dimensions of entrepreneurial marketing which include proactiveness, opportunity-focused, risk-taking orientation, innovation-oriented, customer intensity, resource leveraging, and value creation have an effect on business performance. Primary data was collected through an online survey method involving 258 SME actors in the creative economy industry in Indonesia who had been running their businesses before and during the Covid-19 pandemic. The sampling method used was non-probability sampling through purposive sampling technique. The results of data analysis with multiple linear regression indicated that the dimensions of entrepreneurial marketing that are proven to have an effect and have an important role in improving the business performance of SMEs in the creative economy industry during the pandemic are innovation-oriented, customer intensity, resource leveraging, and value creation, while proactiveness, opportunity-focused, and risk-taking orientation were found to have no effect on business performance.Keywords: entrepreneurial marketing, business performance, small and medium enterprises, creative economy industry, Covid-19 pandemic. Abstrak: Pendekatan entrepreneurial marketing menjadi pilihan strategi yang dapat diadopsi oleh pelaku UMKM untuk terus bertahan khususnya di tengah situasi pandemi Covid-19. Penelitian ini bertujuan untuk mengidentifikasi dimensi-dimensi entrepreneurial marketing mana yang memiliki peran penting bagi peningkatan business performance UMKM di industri ekonomi kreatif pada masa pandemi Covid-19. Secara khusus, penelitian ini menguji apakah dimensi-dimensi entrepreneurial marketing yang mencakup proactiveness, opportunity-focused, risk-taking orientation, innovation-oriented, customer intensity, resource leveraging, dan value creation berpengaruh terhadap business performance. Data primer dikumpulkan melalui metode survei online yang melibatkan 258 pelaku UMKM di industri ekonomi kreatif di Indonesia yang telah menjalankan bisnisnya pada waktu sebelum dan selama pandemi Covid-19. Metode pengambilan sampling menggunakan nonprobability sampling melalui teknik purposive sampling. Hasil analisis data dengan regresi linier berganda menunjukkan bahwa dimensi-dimensi entrepreneurial marketing yang terbukti berpengaruh dan memiliki peran penting bagi peningkatan business performance UMKM di industri ekonomi kreatif selama masa pandemi adalah innovation-oriented, customer intensity, resource leveraging, dan value creation, sedangkan proactiveness, opportunity-focused, dan risk-taking orientation ditemukan tidak berpengaruh terhadap business performance.Kata Kunci: entrepreneurial marketing, business performance, UMKM, industri ekonomi kreatif, pandemi Covid-19.